Efforts to Improve Learning Outcomes of Class V Students Using Interactive Powerpoint Media - Ardiansyah, Ilham (Universitas Sebelas Maret, 2020)
The background of this study is the low learning outcomes of students as evidenced by the low score of evaluation test results. The goal to be achieved is the use of interactive powerpoint media to improve student learning outcomes. The effort made by the writer is improving learning by using interactive powerpoint learning media. This research method uses classroom action research which takes place in three cycles, each cycle consisting of 1) planning; 2) action, 3) observation and 4) reflection. The subjects of this study were 24 students of grade V SD Negeri Cawitali 03. Efforts to improve learning have been successful and end in the third cycle. This can be seen in Cycle I, students who complete learning are 16 students from 24 students = 67%, Cycle II students who complete learning are 19 students out of 24 students = 79.2% and Cycle III students who complete learning are 23 students out of 24. Students = 95.8%. Based on the results obtained, it can be concluded that the learning outcomes of the circulatory system material in grade V SD Negeri Cawitali 03 can be increased by using interactive powerpoint media